1130 The neurological sequelae of the measles outbreak in South Africa. Issue 3 (9th February 2012) - Albertyn, C; Hardie, D; Van der Plas, H; Candy, S; Pan, E Lee; Heckmann, J
Abstract : Introduction: South Africa experienced a measles outbreak in early 2010. Measles may affect the central nervous system early as meningo-encephalitis; months later as subacute measles encephalitis (SME); or years later as subacute sclerosing panencephalitis. SME is typically seen in immunocompromised patients and is characterised by seizures and altered mental status and carries a high mortality. It is an elusive diagnosis and usually confirmed on brain biopsy. Patients and Results: Nine patients were diagnosed with SME between July and October 2010 at our tertiary referral hospital. All patients were HIV positive, with a median CD4 lymphocyte count of 37. All patients had epilepsia partialis continua during the course of the illness and other common features included visual loss, hearing loss, encephalopathy and generalised seizures. Strikingly, CSF examination was normal in all patients and CT Brain imaging was normal in all but one patient. MRI Brain demonstrated superficial grey matter abnormalities in all patients. EEG showed periodic epileptiform discharges in seven patients. Diagnosis was confirmed by brain biopsy in one patient, by post-mortem examination in three patients and by supportive laboratory findings (positive measles PCR and/ or measles antibodies in urine or CSF) in the remainder. The outcome was fatal in seven of the cases. Conclusion: This is the largest SME case series to date and is seen in the aftermath of a measles outbreak in South Africa. Immunocompromised patients are most susceptible and typically present with epilepsia partialis continua. In the absence of a brain biopsy, we propose the use of measles virus PCR in urine and CSF.